THU0327 The Spectrum of Inflammatory Ocular Involvement in Systemic Lupus Erythematosus in a Multidisciplinary Uveitis Unit. (23rd January 2014) - Espinosa, G.; Pelegrin, L.; Montehermoso, A.; Figueras, M.; Sainz de la Maza, M. T.; Sanchez-Dalmau, B.; Molins, B.; Llorens, V.; Mesquida, M.; Adan, A.; Cervera, R.
Abstract : Background: Systemic lupus erythematosus (SLE) can affect all structures of the eye and ocular adnexa. The most common ocular findings include dry eye and retinal vascular changes. Objectives: To describe the inflammatory ocular manifestations of patients with systemic lupus erythematosus (SLE) at a multidisciplinary uveitis unit. Methods: Retrospective chart review of patients with SLE in a tertiary referral center between 2007 and 2012 was performed. All patients have undergone complete rheumatologic and ophthalmic examination including visual acuity, slit-lamp examination of the anterior segment and fundus examination. Fluorescein angiography and optical coherence tomography were performed if they were required. Results: Twenty-three patients presented inflammatory ocular manifestations related to SLE. Patients complained of ophthalmologic disturbances with blurry vision and ocular redness as the most common symptoms. A decrease in the visual acuity was detected in 16 patients (69.6%) mostly due to retinal involvement, optic neuritis and anterior uveitis. Anterior uveitis was found in 8 patients (34.8%), peripheral ulcerative keratitis in 1 patient and diffuse scleritis in 4 patients (17.4%). Changes in retina were found in 7 patients (30.4%); the most frequent was retinal vein occlusion (central retinal vein occlusion in 2 patients and branch retinal vein occlusion in 2 patients) followed by hypertensive retinopathy with serous retinal detachment in 1 patient, occlusive vasculopathy in 1 patient and central serous choroidopathy due to corticosteroids in 1 patient. Three patients (13%) showed neuro-ophthalmological symptoms, 1 patient showed rotatory nistagmus related to central nervous system involvement, 1 patient showed optic neuritis and the remaining presented bitemporal hemianopsy. Conclusions: Ocular manifestations in SLE can affect any structure in the eye. The most visually devastating damage occurs secondary to optic nerve involvement and retinal vaso-occlusion. Anterior uveitis is not an uncommon manifestation of SLE; physicians must be aware of this involvement since it can be treated without serious visual loss. Disclosure of Interest: None Declared